Molecular analysis and prenatal diagnosis of seven Chinese families with genetic epilepsy - Mao, Bin; Lin, Na; Guo, Danhua; He, Deqin; Xue, Huili; Chen, Lingji; He, Qianqian; Zhang, Min; Chen, Meihuan; Huang, Hailong; Xu, Liangpu (Frontiers in Neuroscience, 2023)
Genetic epilepsy is a large group of clinically and genetically heterogeneous neurological disorders characterized by recurrent seizures, which has a clear association with genetic defects. In this study, we have recruited seven families from China with neurodevelopmental abnormalities in which epilepsy was a predominant manifestation, aiming to elucidate the underlying causes and make precise diagnosis for the cases. Whole exome sequencing (WES) combined with Sanger sequencing was used to identify the causative variants associated with the diseases in addition to essential imaging and biomedical examination. A gross intragenic deletion detected in MFSD8 was investigated via gap-polymerase chain reaction (PCR), real-time quantitative PCR (qPCR) and mRNA sequence analysis. We identified eleven variants in seven genes (ALDH7A1, CDKL5, PCDH19, QARS1, POLG, GRIN2A and MFSD8) responsible for genetic epilepsy in the seven families, respectively. Six variants (c.1408T>G in ALDH7A1, c.1994_1997del in CDKL5, c.794G>A in QARS1, c.2453C>T in GRIN2A, and c.217dup and c.863+995_998+1480del in MFSD8) have not yet been reported to be associated with diseases, and were all evaluated to be pathogenic or likely pathogenic according to the American College of Medical Genetics and Genomics (ACMG) guidelines. Based on the molecular findings, we have associated the intragenic deletion in MFSD8 with the mutagenesis mechanism of Alu-mediated genomic rearrangements for the first time, and provided genetic counseling, medical suggestions and prenatal diagnosis for the families. In conclusion, molecular diagnosis is crucial to obtain improved medical outcomes and recurrence risk evaluation for the genetic epilepsy.